Differentiated Vulvar Intraepithelial Neoplasia-like and Lichen Sclerosus-like Lesions in HPV-associated Squamous Cell Carcinomas of the Vulva. (June 2018) - Rakislova, Natalia; Alemany, Laia; Clavero, Omar; del Pino, Marta; Saco, Adela; Quirós, Beatriz; Lloveras, Belen; Alejo, Maria; Halec, Gordana; Quint, Wim; de Sanjosé, Silvia; Ordi, Jaume
Abstract : Most human papillomavirus (HPV)-associated vulvar squamous cell carcinomas (VSCCs) originate from high-grade squamous intraepithelial lesions, also named usual type vulvar intraepithelial neoplasia. However, growing evidence suggests that morphologic studies have limitations in predicting HPV status in vulvar lesions. We aimed to evaluate adjacent intraepithelial lesions in a series of DNA HPV-positive VSCCs, focusing on unusual histologic patterns mimicking differentiated vulvar intraepithelial neoplasia (dVIN) or lichen sclerosus (LS). We identified 326 DNA HPV-positive VSCC with at least 1 cm of skin adjacent to the invasive tumor and analyzed HPV typing, HPV E6*I mRNA, and p16 immunohistochemistry in all cases. A careful histologic evaluation was conducted. A conclusive association with HPV was based on a positive p16 or HPV E6*I mRNA result or both in addition to the HPV DNA, whereas cases negative for both markers were classified as nonconclusively associated with HPV. One hundred twenty-one tumors (37.1%) had normal adjacent skin, 191 (58.6%) had only high-grade squamous intraepithelial lesions, also named usual type vulvar intraepithelial neoplasia, and unusual intraepithelial lesions were identified in 14 (4.3%) tumors. Seven cases showed dVIN-like features, 5 showed adjacent LS-like lesion, and in 2 cases dVIN-like and LS-like lesions were identified simultaneously. Six of them were conclusively associated with HPV (3 dVIN-like, 2 LS-like, 1 with combined dVIN/LS-like features). All 6 tumors were associated with HPV16 and were positive for both p16 and HPV mRNA, and p16 was also positive in the dVIN-like and LS-like lesions. In summary, a small subset of VSCCs conclusively associated with HPV may arise on intraepithelial lesions, mimicking precursors of HPV-independent VSCC.